A Review of Spectroscopic and Biophysical‐Chemical Studies of the Complex of Cyclobutane Pyrimidine Dimer Photolyase and Cryptochrome DASH with Substrate DNA1. (20th January 2017) - Schelvis, Johannes P. M.; Gindt, Yvonne M.
Abstract: Cyclobutane pyrimidine dimer (CPD) photolyase (PL) is a structure‐specific DNA repair enzyme that uses blue light to repair CPD on DNA. Cryptochrome (CRY) DASH enzymes use blue light for the repair of CPD lesions on single‐stranded (ss) DNA, although some may also repair these lesions on double‐stranded (ds) DNA. In addition, CRY DASH may be involved in blue light signaling, similar to cryptochromes. The focus of this review is on spectroscopic and biophysical‐chemical experiments of the enzyme–substrate complex that have contributed to a more detailed understanding of all the aspects of the CPD repair mechanism of CPD photolyase and CRY DASH. This will be performed in the backdrop of the available X‐ray crystal structures of these enzymes bound to a CPD‐like lesion. These structures helped to confirm conclusions that were drawn earlier from spectroscopic and biophysical‐chemical experiments, and they have a critical function as a framework to design new experiments and to interpret new experimental data. This review will show the important synergy between X‐ray crystallography and spectroscopic/biophysical‐chemical investigations that is essential to obtain a sufficiently detailed picture of the overall mechanism of CPD photolyases and CRY DASH proteins. Abstract : This paper reviews the progress that has been made in our understanding of the enzyme–substrate complex formation between DNA photolyase and UV‐damaged DNA and between cryptochrome DASH and UV‐damaged DNA. In addition, the changes that occur in the physicochemical properties of the enzyme upon substrate binding are also reviewed. The emphasis of this review is on those studies that have used spectroscopic, thermodynamic and electrochemical techniques to study the enzyme–substrate complex and its formation. In addition, a complete thermodynamic cycle for the repair of cyclobutane pyrimidine dimers by DNA photolyase and cryptochrome DASH is presented.